A retrospective comparison of propofol alone to propofol in combination with dexmedetomidine for pediatric 3T MRI sedation. Issue 1 (25th October 2016) - Boriosi, Juan P.; Eickhoff, Jens C.; Klein, Kristi B.; Hollman, Gregory A.
Abstract: Background and aim: Both propofol and dexmedetomidine have been found to be safe and effective sedation for magnetic resonance imaging (MRI). Our program experienced an increase in patients arousing and experiencing an adverse airway event during propofol sedation for MRI in the first months of using a new 3T (Tesla) MRI scanner that was found to have a longer reverberation time compared to the previous 1.5 T MRI. In an effort to decrease patient arousal and adverse airway events during MRI, we administered a dexmedetomidine load prior to our standard propofol protocol. The objective was to compare adverse events and other outcome measures of patients sedated with propofol alone (Pro) and propofol preceded by a dexmedetomidine load (D+P). Methods: We reviewed a sedation database and medical records for all children undergoing 3T MRI studies while sedated with propofol alone or propofol preceded by a dexmedetomidine load in 2014. Results: Two hundred and fifty‐six sedations were performed for MRI (87 Pro and 169 D+P). The two groups were comparable with regard to age, weight, gender, and American Society of Anesthesiologists status. Subjects in the D+P cohort had significantly fewer adverse events (10/169 patients (5.9%) vs 23/87 patients (26.4%) [OR 0.18, 95% CI: 0.08–0.39, P  < 0.001]), particularly upper airway obstruction. Mean discharge time was longer in the D+P cohort compared to the Pro cohort (87.1, SD 26.3 min vs 69.7, SD 23.6; [mean difference 17.7 min, 95% CI: 10.6–24.8, P  < 0.001]). Conclusions: The addition of a dexmedetomidine infusion prior to our propofol MRI sedation protocol resulted in fewer sedation‐related adverse events, particularly upper airway obstruction. Further studies are needed to evaluate the potential for a reduction on adverse events with this drug combination. Abstract :